The impact of corporate governance on the objectives of internal accounting control in the Jordanian commercial banks sector - Al-Abdallat, Samer Nahar; Benamr, Fatiha; Bidiyah, Hind (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to identify the impact of corporate governance on the objectives of internal accounting control in the Jordanian commercial banks sector. The study relied on the descriptive analytical approach, and the study sample consisted of (164) male and female employees working in the internal control department in Jordanian commercial banks. A questionnaire was used to collect data, which included two areas: corporate governance and internal accounting control objectives. The results showed a statistically significant impact of the principles of corporate governance on the effectiveness and efficiency of accounting operations, and the presence of a statistically significant impact of the principles of corporate governance on the reliability and completeness of financial reports, and the presence of a statistically significant impact of the principles of corporate governance on consistency with laws and legislation.
Keywords: Corporate governance; internal accounting control; commercial banks